Metamaterial inspired electromagnetic applications : role of intelligent systems - Choudhury, Balamati (Springer, 2017)
This book focuses on the role of soft-computing-based electromagnetic computational engines in design and optimization of a wide range of electromagnetic applications. In addition to the theoretical background of metamaterials and soft-computing techniques, the book discusses novel electromagnetic applications such as tensor analysis for invisibility cloaking, metamaterial structures for cloaking applications, broadband radar absorbers, and antennas. The book will prove to be a valuable resource for academics and professionals, as well as military researchers working in the area of metamaterials.
Keywords: Metamaterials.; Electromagnetism.; Electromagnetic devices.; elektronické knihy; electronic books